SPATIAL INTEGRATION OF VEGETABLE WHOLESALE MARKETS IN POLAND ON THE SELECTED EXAMPLE - Sobczak, Wioleta; Borkowski, Bolesław; Zbyrowski, Rafał (Acta Scientiarum Polonorum. Oeconomia, 2018)
This article attempts to verify the phenomenon of price transmission between wholesale markets of carrots in Poland. Determining the level of spatial integration of markets will indicate their efficiency and thus can make it easier for producers to take decisions about where to sell their products. The empirical data includes daily quotations of carrot prices on fruit and vegetable wholesale markets in Bronisze, Kalisz, Poznań, Radom and Sandomierz. The time range of the studies covered the years 2011–2016. This research is based on dynamic econometric methods (sVAR model) and the Granger causality tests. The research carried out using dynamic econometric methods has shown that despite the occurrence of significant variation in the level of carrot prices in the examined markets, their interaction was observed. Moreover, the results of the sVAR model estimation indicate that the changes in carrot prices on a particular market are stronger influenced by the price changes from the same market. This is an autoregressive effect. It also means that the carrot price information coming from other wholesale markets (price transmission effect) has a much weaker effect.